2021
DOI: 10.3389/fgene.2021.740216
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Barriers and Enablers to the Implementation of Pharmacogenetic Testing in Mental Health Care Settings?

Abstract: In psychiatry, the selection of antipsychotics and antidepressants is generally led by a trial-and-error approach. The prescribing of these medications is complicated by sub-optimal efficacy and high rates of adverse drug reactions (ADRs). These both contribute to poor levels of adherence. Pharmacogenetics (PGx) considers how genetic variation can influence an individual’s response to a drug. Pharmacogenetic testing is a tool that could aid clinicians when selecting psychotropic medications, as part of a more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 66 publications
1
47
0
Order By: Relevance
“…Few centers have formalized processes for clinical PGx testing due to several implementation challenges [ 28 , 29 ]. Our latent class analysis of the BWS ranking of CFIR constructs in centers that have implemented or are planning to implement PGx testing aligns with the results of previous studies that have reported on facilitators and barriers of PGx implementation [ 17 , 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few centers have formalized processes for clinical PGx testing due to several implementation challenges [ 28 , 29 ]. Our latent class analysis of the BWS ranking of CFIR constructs in centers that have implemented or are planning to implement PGx testing aligns with the results of previous studies that have reported on facilitators and barriers of PGx implementation [ 17 , 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The RCTs that have evaluated PGx-guided versus unguided (standard) prescribing in psychiatry have been sponsored by commercial laboratories and most have utilized proprietary combinatorial testing, raising concerns about conflicts of interest and transparency, respectively. 38 A meta-analysis of five…”
Section: Uncertainty About Clinical Efficacy and Cost-effectivenessmentioning
confidence: 99%
“…The most consistent hurdles to PGx testing identified by numerous studies 29,[35][36][37][38]72,73 are knowledge and education gaps among physicians, pharmacists, genetic counsellors, nurse practitioners, and the public. Studies to date suggest that 80%-90% of health-care professionals agree about the value of PGx testing in drug selection and dose optimization; however, only 10%-20% are properly trained or confident enough to routinely use PGx testing in their practice.…”
Section: Knowledge and Education Gapsmentioning
confidence: 99%
“…Education, training and clinical informatics represent some of the greatest challenges to widespread adoption. Prescribers require clear, simple, clinically relevant information at the point of prescribing to facilitate implementation 11 . Incorporating models of care, where pharmacologists, pharmacists and other healthcare professionals work in multidisciplinary teams providing PGx interpretation, could support primary care doctors to improve patient care without additional workload 12 …”
Section: The Futurementioning
confidence: 99%